1999
DOI: 10.1007/s004310051122
|View full text |Cite
|
Sign up to set email alerts
|

Lack of lymphoid cell apoptosis in the pathogenesis of tonsillar hypertrophy as compared to recurrent tonsillitis

Abstract: Whereas recurrent tonsillitis is characterised by apoptotic death of lymphoid tissue, tonsillar hypertrophy is caused by environmental pollution agents that trigger the chronic inflammatory process without apoptotic cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
3
19
1
3
Order By: Relevance
“…The pathogenesis of tonsils and adenoid hypertrophy is unknown and lacks a proper infectious or immunological explanation [7]. It is also known, that the children's tonsils have a greater concentration of immune cells than adults' tonsils [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of tonsils and adenoid hypertrophy is unknown and lacks a proper infectious or immunological explanation [7]. It is also known, that the children's tonsils have a greater concentration of immune cells than adults' tonsils [17].…”
Section: Discussionmentioning
confidence: 99%
“…The lymphoreticular tissues of tonsils and adenoids are directly exposed to the outside environment [3][4][5]. The importance of interleukins (IL-2, IL-4, IL-10 and IL-12), interferon-g (IFNg), and cachectin-a (TNFa) in controlling and/or enhancing the local immune response in nasopharyngeal lymphoid tissue has been well documented [1,[6][7][8][9]. The selection of effector immune functions is controlled by antigen-specific Thelper cells, which secrete Th1-and Th2-type cytokines at different ratios.…”
Section: Introductionmentioning
confidence: 99%
“…After repeated antigen challenge, chronic recurrent tonsillitis with or without tonsillar hypertrophy may develop. The pathogenic mechanism of tonsillar hypertrophy has not yet been elucidated, although recently it has been reported that there is a reduction of apoptotic death of lymphoid tissue [4].…”
Section: Discussionmentioning
confidence: 99%
“…+ macrophages containing peptidoglycan, thought to have originated in the tonsils, have been found in increased numbers in psoriatic skin lesions [52], and lesional CD4 + T cell clones have been shown to respond in an HLArestricted manner to this streptococcal peptidoglycan [52]. Thus, the recurrent tonsil infections could lead to the maturation of skin-homing T cells that recognize streptococcal membrane and cell wall moieties [55] which, after migration to the skin, could react with streptococcal epitopes [52] or alternatively skin-specific epitopes via molecular mimicry [18,56], leading to the development of psoriasis plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the recurrent tonsil infections could lead to the maturation of skin-homing T cells that recognize streptococcal membrane and cell wall moieties [55] which, after migration to the skin, could react with streptococcal epitopes [52] or alternatively skin-specific epitopes via molecular mimicry [18,56], leading to the development of psoriasis plaques.…”
Section: Discussionmentioning
confidence: 99%